High-resolution imaging of surface acoustic wave scattering - Hesjedal, T; Behme, G (2001)
We examine the scattering of surface acoustic waves (SAWs) by single dots, periodic and locally damped two-dimensional dot lattices. Employing the scanning acoustic force microscope, SAW fields are imaged with nanometer resolution. We study the influence of a roughly wavelength-sized single dot on SAW diffraction. In order to distinguish between forward- and backscattered components, we insonify the dot with the pump and probe beam under 0° and 90°. We furthermore analyse the SAW diffraction by a regular dot array. The wave field appears to be localized around the dots. Adding surface distortions, the regular SAW localization pattern brakes down in the vicinity of the distortion. © 2001 American Institute of Physics.